Cartographic grounds : the temporal cases (2019)
A map is inherently static and out-of-date. In the translation of information from the real world to the projected image there is a time-lapse. Even in the most realtime applications, there exists a lag. Thus, the map describes the near past — or even the far past intentionally in the case of historic maps — while often contributing to a reading, and even constructing, of a future. These relationships to time beg two questions: how is time implicit in the production of cartographic and design drawings? And what are the methods of explicitly introducing time onto the map and the plan, to contend with static representations of dynamic conditions? In order to investigate these questions, I will focus on two specific types of drawing: the topographic map and the design plan. Maps are too easily mistaken for objective depictions of a present-day geographical condition, and their complexity often obscures the fact that they are, in fact, distortions. Their uses, limitations, and subjectivity must be understood and respected. Distortion can stem from the underlying data, editorial choices, and representational method. This distortion relates to time and space. Maps of a particular place often rely on data collected from different sources and time periods, but represent the space as if the underlying data were uniform (Kurgan 2013). Maps utilise a set of malleable yet rigorously defined representational techniques capable of persuasion, description, and, above all, projection.